Comparing the quality of life and satisfaction with treatment of type 2 diabetes patients who participated in the Waan Chean Jai with patients who did not participated - Pitaksinpanit, Vitchapon (Journal of Preventive Medicine Association of Thailand, 2020)
The objective of this research was to study the quality of life and satisfaction with treatment of type 2 diabetes patients who participated in the Waan Chean Jai which is self-management education and support project of the Saraburi Hospital comparing with type 2 diabetes patients who did not participate in the project. The research model was a cross-sectional analytical study by using the sample groups from out-patient department of Saraburi hospital 206 persons which can be divided into 2 groups as follows: 1.Participated program at least 3 months 2. Not participated program. The used instruments were Audit of Diabetes Dependent Quality of Life 19 (ADDQoL19) and Diabetes Treatment Satisfaction Questionnaire (DTSQ). The finding revealed that type 2 diabetes patients who participated in the Waan Chean Jai had the average blood sugar level after fasting for 8 hours (FBS), the cumulative average of the sugar (HbA1C) were significantly lower with a P-Value <0.001 and <0.001 respectively. In addition, patients who participated in the project had a higher level of the mean and average quality of life than patients who did not participated in the program (p<0.001) and found that the overall satisfaction from treatment was higher than patients who did not participate in the activity at a statistically significant (p<0.001). Therefore, doctors and concerned personnel should educate people with diabetes and strengthen their diabetes care skills in combination with general diabetes treatment so that patients can control their blood sugar levels according to their goals and enhance the quality of life, including satisfaction with existing diabetes treatment and reducing future in current disease of patients.